Использование аптамеров для увеличения параметров биосовместимости пористых материалов на основе TiNi - Аникеев, Сергей Геннадьевич (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The present work is aimed at determining the types of aptamers compatible with porous alloys based on titanium nickelide, which can be used to increase biocompatibility parameters. As a result of the analysis of the literature data, it was found that there are a number of problems that limit the introduction of aptamers into practice. There is a known technique using a PEG solution, to which an aqueous or buffer solution of one or more aptamers (5 mg/ml) with an activating effect on the αvβ3 integrin receptor was added at room temperature.